Prevention of Infections in Peritoneal Dialysis: Survey Among Young Tunisian Nephrologists - Meriam Khadhar; Hanene Gaied; Mouna Jerbi; Sarra Haddad; Asma Bettaieb; Raja Aoudia; Rim Goucha (Bulletin de la Dialyse à Domicile)
Peritonitis is a severe complication in peritoneal dialysis (PD) patients, contributing to technique failure and patient mortality. Tunisia lacks a national dialysis registry, making the incidence of peritonitis unclear. The International Society for Peritoneal Dialysis (ISPD) published guidelines from 2016 to 2022, outlining effective strategies for preventing infections in PD patients. This study was conducted between June and July 2022 to assess Tunisian nephrologists’ knowledge and practices for preventing infections. Using an online questionnaire, 44 participants (67.69% response rate) provided insights. Findings revealed an average score of 4.45 out of 7, indicating significant confusion among respondents. Many incorrectly believe that protecting the catheter under the skin until renal replacement therapy is initiated reduces infections. Questions also addressed nasal Staphylococcus aureus screening, antibiotic prophylaxis, surgical techniques, timing of dressing changes, and local antibiotic use. Responses varied, with 59.1% supporting systematic nasal screening but differing concerning eradication strategies. The study highlights discrepancies between current practices and ISPD guidelines among young Tunisian nephrologists. Recommendations include establishing a national dialysis registry to enhance surveillance and developing tailored national guidelines. A working group from the Tunisian Society of Nephrology, Dialysis, and Transplantation is already developing protocols to address identified gaps and improve PD patient outcomes.